2021
DOI: 10.35808/ersj/1989
|View full text |Cite
|
Sign up to set email alerts
|

Mobbing in Banks: The Role of Gender and Position on the Process of Mobbing in Banks in Poland and Russia

Abstract: Purpose: The main purpose of this paper is to determine the scale of mobbing in banks, in particular we seek to investigate who is the most frequently a mobber and who is most often affected by mobbing. Approach/Methodology/Design: English and Polish literature from EBSCO, ProQuest, and Emerald databases were used to write the article. The methods that were used for the study were classification trees, the Mann-Whitney test, and descriptive statistics. Findings: This paper presents the results of an empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In fact, both security guards and production workers are low-ranked workers at Company A but they were placed into two confrontational positions. As Kazmierczyk suggests, mobbing and bullying more likely occur within employees/workers at a similar level and this kind of non-hierarchical mobbing has even greater detrimental effects on workers’ well-being [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, both security guards and production workers are low-ranked workers at Company A but they were placed into two confrontational positions. As Kazmierczyk suggests, mobbing and bullying more likely occur within employees/workers at a similar level and this kind of non-hierarchical mobbing has even greater detrimental effects on workers’ well-being [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, they also revealed that “a minority of men had found ways of being masculine which were outside hegemonic discourses” and therefore escaped from the trap of hegemonic masculinity that constrained them [ 22 ] (p. 2246). Similarly, Kazmierczyk et al’s study of mobbing at the workplace also showed that men are more often the victims of mobbing/bullying as compared to women, as “men cope worse with criticism or a lack of appreciation” [ 24 ] (p. 710).…”
Section: Incorporating Masculinity and Religion Into Workplace Well-beingmentioning
confidence: 99%